Altered gene expression of the innate immune, neuroendocrine, and nuclear factor-kappa B (NF-κB) systems is associated with posttraumatic stress disorder in military personnel. (March 2016) - Guardado, Pedro; Olivera, Anlys; Rusch, Heather L.; Roy, Michael; Martin, Christiana; Lejbman, Natasha; Lee, Hwyunhwa; Gill, Jessica M.
Highlights: A total of 203 genes were differentially expressed in military personnel with PTSD. Findings were independent of depression severity, history of TBI, and meditation use. IPA identified dysregulated innate immune, glucocorticoid receptor, and NF-κB pathways. The PTSD group showed upregulation in pro-inflammatory cytokine genes. Findings suggest that inflammation may be a significant factor in PTSD pathogenesis. Abstract: Whole transcriptome analysis provides an unbiased examination of biological activity, and likely, unique insight into the mechanisms underlying posttraumatic stress disorder (PTSD) and comorbid depression and traumatic brain injury. This study compared gene-expression profiles in military personnel with PTSD ( n  = 28) and matched controls without PTSD ( n  = 27) using HG-U133 Plus 2.0 microarrays (Affymetrix), which contain 54, 675 probe sets representing more than 38, 500 genes. Analysis of expression profiles revealed 203 differentially expressed genes in PTSD, of which 72% were upregulated. Using Partek Genomics Suite 6.6, differentially expressed transcription clusters were filtered based on a selection criterion of ≥1.5 relative fold change at a false discovery rate of ≤5%. Ingenuity Pathway Analysis (Qiagen) of the differentially expressed genes indicated a dysregulation of genes associated with the innate immune, neuroendocrine, and NF-κB systems. These findings provide novel insights that may lead to new pharmaceutical agents for PTSD treatments and help mitigate mental and physical comorbidity risk.